Kapampangan intangible cultural heritage documentation and archiving practices - Martin, Amor C. (2009)
This study looked into the available documentations and archiving practices of cultural repositories or centers in Pampanga. Spiraling and eclectic approaches were the researcher's guiding principles in constructing the design of the study. It involved different methodology for every type of data. It utilized survey-documentary analytical method in identification of available documentations and record Kapampangan Intangible Cultural Heritage (KICH). Face-to-face interview was conducted in collecting information about the archiving practices of target respondents.